Apparent ileal nitrogen digestibility and apprent metabolizable energy corrected to zero nitrogen in broiler chickens fed textured diets and feed restricted at different ages - Urdaneta Rincón, María; Leeson, Steven; Arzalluz, Ana María; Rincón, Hirwin (Revista Científica de la Facultad de Ciencias Veterinarias)
Two experiments were carried out to evaluate the apparent nitrogen digestibility and the apparent metabolizable energy in broiler chickens fed textured diets and feed restricted. Chicks in experiment 1 were housed in an electrically heated brooder battery and fed ad libitum or feed-restricted to 90% of birds fed ad libitum intake of previous day. Chromic oxide was used as a marker. Birds at 15 d of age were killed and the ileal digesta collected for nitrogen digestibility and AMEn. The apparent nitrogen digestibility was no significantly different (P > 0.05) between ad libitum (78.9%) and feed-restricted (79.3%) broilers at 15 days of age. There was no difference (P > 0.05) for the apparent metabolizable energy corrected to zero nitrogen (AMEn) between treatments. Chicks in the second experiment were housed in batteries or cages depending on age of the bird. Birds were fed with diets pelleted, mashed or pelleted but feed-restricted to 90% of ad libitum intake. Excreta was collected and wrapped in aluminum foil trays over 72 h, and dried at 65°C. Samples were assay for gross energy and nitrogen evaluations. The AMEn was significantly different (P < 0.01) among chicks fed crumble (3061 Kcal/kg), mash (2994 Kcal/kg), or feed restricted to 90% of ad libitum crumble intake (3087 Kcal/kg). In broiler chickens at 28 and 48 days of age, there were no significant differences (P > 0.05) in the AMEn when fed crumble (3355 and 3357 Kcal/kg), mash (3344 and 3348 Kcal/kg) or feed restricted (3332 and 3356 Kcal/kg) to 90% of ad libitum texture diets intake respectively. It was concluded that mild feed restriction does not influence ileal nitrogen digestibility or AMEn in young broilers. Texture of diets only affected (P < 0.05) the AMEn at early age of birds.